Numerical model of quantum oscillations in quasi-two-dimensional organic metals in high magnetic fields. - Harrison, N; Bogaerts, R; Reinders, P; Singleton, J; Blundell, S; Herlach, F (1996)
Departures from standard Lifshitz-Kosevich behavior observed in the oscillatory magnetization and magnetoresistance of bis(ethylenedithio)tetrathiafulvalene (BEDT-TTF) charge-transfer salts in high magnetic fields are investigated using a numerical model of the Landau levels in a quasi-two-dimensional metal. The numerical model enables oscillations in the chemical potential to be treated, as well as the effects of finite temperature, Landau level broadening, and the presence of additional quasi-one-dimensional Fermi surface sheets. The numerical calculations reproduce experimental magnetization data successfully, and allow several phenomena observed in the experiments to be investigated. It is found that pinning of the chemical potential to the Landau levels is responsible for the apparent anomalously low effective masses of the higher harmonics of the de Haas-van Alphen oscillations observed in recent experiments. In addition, the quasi-one-dimensional components of the Fermi surface are found to have a pronounced influence on the wave form of the oscillations in the model, providing a means by which their density of states can be estimated from experimental results. Whilst the magnetization is a thermodynamic function of state, calculations of the behavior of the magnetoresistance are much more model dependent. In this paper, recent theoretical models for the longitudinal magnetoresistance in semiconductor superlattices have been modified for use with the BEDT-TTF salts and are shown to successfully reproduce the form of the experimental data. The strongly peaked structure of the magnetoresistance, which comes about when the chemical potential is situated in or close to the gap between adjacent Landau levels, is found to be responsible for the apparent strong increase of the effective mass which has recently been reported in high field transport measurements.